Divergent effects of EZH1 and EZH2 protein expression on the prognosis of patients with T-cell lymphomas - Schümann, Franziska Lea; Groß, Elisabeth; Bauer, Marcus; Rohde, Christian; Sandmann, Sarah; Terziev, Denis; Müller, Lutz P.; Posern, Guido; Wienke, Andreas; Fend, Falko; Hansmann, Martin-Leo; Klapper, Wolfram; et al. (Biomedicines, 2021)
T-cell lymphomas are highly heterogeneous and their prognosis is poor under the currently available therapies. Enhancers of zeste homologue 1 and 2 (EZH1/2) are histone H3 lysine-27 trimethyltransferases (H3K27me3). Despite the rapid development of new drugs inhibiting EZH2 and/or EZH1, the molecular interplay of these proteins and the impact on disease progression and prognosis of patients with T-cell lymphomas remains insufficiently understood. In this study, EZH1/2 mutation status was evaluated in 33 monomorphic epitheliotropic intestinal T-cell lymphomas by next generation sequencing and EZH1/2 and H3K27me3 protein expression levels were detected by immunohistochemistry in 46 T-cell lymphomas. Correlations with clinicopathologic features were analyzed and survival curves generated. No EZH1 mutations and one (3%) EZH2 missense mutation were identified. In univariable analysis, high EZH1 expression was associated with an improved overall survival (OS) and progression-free survival (PFS) whereas high EZH2 and H3K27me3 expression were associated with poorer OS and PFS. Multivariable analysis revealed EZH1 (hazard ratio (HR) = 0.183; 95% confidence interval (CI): 0.044-0.767; p = 0.020;) and EZH2 (HR = 8.245; 95% CI: 1.898-35.826; p = 0.005) to be independent, divergent prognostic markers for OS. In conclusion, EZH1/2 protein expression had opposing effects on the prognosis of T-cell lymphoma patients.
Gesehen am 21.07.2022